Enhancing Therapeutic Potential: Investigating Traditional Detoxification Methods and Assessing their Influence on Anti-Microbial Efficacy, Phytochemical Composition, Heavy Metal Content and Anti-inflammatory Properties in Trachyspermum ammi - Vanitha, Kalkatanur Ganesan; Anandakumar Natarajan, N.; Sudhakar, Natesan; Hirad, Abdurahman Hajinur; Alarfaj, Abdullah A.; Arulselvan, Palanisamy; Raja, Rathinam (Indian Journal of Pharmaceutical Education and Research, 2024)
Background Trachyspermum ammi (T. ammi) holds a longstanding position in traditional medicinal practices, renowned for its diverse medicinal and pharmacological attributes. Medicinal plants not only offer significant therapeutic benefits but also hold economic importance. A noteworthy trait of phytomedicine lies in its low toxicity, which positively impacts the pharmaceutical market. Hence, traditional practices often incorporate detoxification/purification methods to mitigate the toxicity of herbs. Objectives Aimed at scientifically validating these practices, our study explores the traditional detoxification method known as Sodhana and assessing its Influence on T ammi. Materials and Methods We evaluate the antimicrobial, phytochemical, heavy metal content and anti-inflammatory efficacy of detoxified T ammi seeds. Results The seeds undergo lime treatment, followed by grinding into powder and extraction with 90% ethanol. Our antimicrobial study reveals that lime-treated ethanol extract exhibits robust inhibitory activity against various microbial strains, surpassing the unprocessed extract in most cases. Notably, significant reductions in heavy metal content are observed post-lime treatment, particularly in titanium, indium, bismuth, strontium, lead, aluminum, boron, mercury, and cadmium. Phytochemical analyses via ICP/OES, GC-MS and LC-MS demonstrate alterations in compound compositions between unprocessed and lime-treated extracts, with the latter exhibiting elevated levels of thymol and fatty acids. Furthermore, our investigation highlights the considerable anti-inflammatory potential of lime-treated T ammi seed extracts. Conclusion In conclusion, our findings emphasize the efficacy of lime treatment in reducing toxic elements while enhancing antimicrobial and anti-inflammatory properties, thus advocating for its utilization in traditional herbal practices.
Keywords: Detoxification; Phytochemical Composition; Anti-inflammatory; Trachyspermum ammi